Superioritas Laki-laki atas Perempuan - M. Zaki Suaidi Zaki (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
The women's movement in Islam is in a dilemmatic position. One group thought there was nothing to argue about with women. While other groups consider the fate of women has not been completed. The first group views that Islam highly upholds the dignity of women. This group usually criticizes the Western-style women's movement which is considered un-Islamic. By stating that there are no similarities between men and women in any way. What exists is similarity in dissimilarity. Because even though there are many similarities that the Qur'an reveals, it turns out that there are many more dissimilarities. In principle, women and men are physically and biologically different. According to them, the best women's movement is the dedication of women in the household, helping husbands as defenders and guardians of family morality. Because the moral crisis that hit the younger generation is caused by the small role of women as guardians, educators and protectors of the household. While the second group, considers the problem of women's fate has not been completed. There are still many aspects that should receive attention. Theoretically and methodologically this group draws on concepts from the West, although sometimes without criticism. This is because Western feminism is more based on a paradigmatic and epistemological movement. However, ideally and normatively this moderate group still uses the Qur'an and Sunnah as the basis of its movement. Therefore, this group does not view the domestic role of women as a setback, as long as it is carried out not by force or coercion by men.